AKTIVITAS KOMUNIKASI ORGANISASI PADA KANTOR URUSAN AGAMA KECAMATAN MALUNDA KABUPATEN MAJENE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
The substance of this research problem is how the activity of organizational communication at the Office of Religious Affairs, Malunda District, Majene Regency, with the sub-problem, namely how is the organizational communication process and what are the supporting factors and obstacles to the course of organizational communication at the Office of Religious Affairs, Malunda District, Majene Regency? This type of research falls into the category of qualitative research with a communication approach. Sources of data used are primary data sources and secondary data sources. The results showed that downward vertical communication was carried out discussing work matters. Upward vertical communication discusses work and non-work matters. Horizontal communication is carried out discussing matters of work and matters outside of work. A more effective method is using Persuasive. The communication channels used are oral, written, and electronic, but verbal is more effective.